Storytelling Workshops Based on Babad Banyumas Stories for Local Tourism Community to Support Storynomics Tourism Development in Banyumas Regency - Dani Kusumastuti; Oki Edi Purwoko (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Storytelling-based tourism or Storynomics tourism is being promoted by the government as a quick win strategy for economic recovery. Banyumas has a valuable historical heritage that is Babad Banyumas. These manuscripts are sources for interesting stories that add the attractiveness of tourist destinations. Unfortunately, the ability of local tour guides in storytelling are still low. Therefore, this training is intended to develop their skills in oral and digital storytelling of Babad Banyumas. The method is active learning that combines lectures, discussions, group assigment and presentation. Storybook and puppet form of figures in Babad Banyumas are provided as instruments for oral storytelling, and cameras and supporting devices for digital storytelling. Based on observation, mostly the participants were able to perform well in oral storytelling. Observation of photos and videos story of participants also showed encouraging result. The results of pre and post tests analysis show that both trainings have had a significant impact on increasing the knowledge and skills of participants. This findings support the idea of functioning community development and tourism strategy as global perfect merge for social economic development.